Fenomena Politik Uang pada Pemilihan Umum Di Indonesia Solusi dan Tantangannya - Ramadhan, Syahru; Rahmawati, Nissa; Sari, Yayu Intan; Ananto, Muh Aldi Musbaq; Sufiarni, Sufiarni (CV. Ulil Albab Corp, 2024)
General elections should be an important stage in social and state life, because in this election, the community is involved or involved as a fundamental element that determines the functioning of democracy. Democracy will its purity is maintained in the hands of election organizers and the people. One phenomenon that often occurs during elections is political crime and legal irregularities that tarnish the image of the democratic party are money politics political). This research aims to analyze the juridical practices of money politics by political elites with the aim of buying people's votes and destructive forms of political behavior government building. The research method used is normative legal research equipped with analytical, conceptualization and comparative approaches by prioritizing data secondary with qualitative analysis. The research results show practice money politics carried out by political elites with the aim of buying people's votes, among others other: money is the root of problems and damage to the building of government and democracy, and the power of the practice of bribery has entered the deepest pores or tissues of life society is proven, both to fight for and reap the values of goodness, justice, and human dignity.